2022
DOI: 10.1111/mec.16582
|View full text |Cite
|
Sign up to set email alerts
|

Delimiting the cryptic diversity and host preferences of Sycophila parasitoid wasps associated with oak galls using phylogenomic data

Abstract: Cryptic species diversity is a major challenge for the species-rich community of parasitoids attacking oak gall wasps due to a high degree of sexual dimorphism, morphological plasticity, small size, and poorly known biology. As such, we know very little about the number of species present, nor the evolutionary forces responsible for generating this diversity. One hypothesis is that trait diversity in the gall wasps, including the morphology of the galls they induce, has evolved in response to selection imposed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 144 publications
0
21
0
Order By: Relevance
“…2022; Zhang et al. 2022). If gall wasps shift hosts, and are followed by concomitant shifts by natural enemies, the ecological dimensions relevant to reproductive isolation in the gall wasp might “cascade” during a host shift and promote reproductive isolation among insect natural enemies (Blair et al.…”
Section: Discussionmentioning
confidence: 99%
“…2022; Zhang et al. 2022). If gall wasps shift hosts, and are followed by concomitant shifts by natural enemies, the ecological dimensions relevant to reproductive isolation in the gall wasp might “cascade” during a host shift and promote reproductive isolation among insect natural enemies (Blair et al.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports that niche specialization by generalist parasitoids with broad host ranges is common in oak gall wasp-parasitoid communities, with richness in parasitoid communities maintained by partitioning of generalist parasitoids among different gall phenotypes (24,42,51). However, with increased molecular studies of parasitoid wasp communities and their interactions, more putative specialists originally described as generalists are being revealed (27,28,53,93,94). Identifying parasitoids via morphological features and taxonomic keys is challenging, and rearing out parasitoids from hosts may lead to incomplete information about associations.…”
Section: Discussionmentioning
confidence: 99%
“…We also measured gall morphotype traits important in defense, such as gall size, internal traits (e.g., woody, fleshy or hollow), and external traits (e.g., nectar-producing, wooly, textured). We scored gall traits using our own observations and other resources (see S1 for details) (53,60,66).…”
Section: Host-parasitoid Interaction Traits and Phenologymentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, other congeneric species can be very hard to distinguish, even for experienced taxonomists, and additionally, molecular data often reveal cryptic species (Cook et al, 2017; Haine et al, 2006; Molbo et al, 2003), as in many other insect taxa (e.g. moths – Hebert et al, 2004; bees – Mayr et al, 2021; and oak gall wasps – Zhang et al, 2022). Consequently, few community‐level studies have identified all wasps to species or even morphospecies level.…”
Section: Introductionmentioning
confidence: 99%